Efektivitas Gel Ekstrak Etanol 70% Daun Anggrek Oncidium (Oncidium Aliceara alice) terhadap Penyembuhan Luka Kulit Dorsum Tikus Sprague Dawley - Onibala, Michele Liony Maria; Suntadi, Maria Ariska Happy; Wiadji, Jovitta Theachrysilla; Oktaviani, Yustina Wanda Dwi; Gunawan, Yohanes Candra; Widhiastuti, Stefani Santi (Pusat Penelitian dan Pengembangan Biomedis dan Teknologi Dasar Kesehatan, 2023)
Wounds are tissue damage that is generally caused by physical contact. Wound healing is a complex mechanism involving biochemical and biocellular processes. Various therapies can be done to speed up the wound healing process, one of which is treatment using natural ingredients. One of the plants that have the potential to heal wounds is Oncidium Aliceara alice. The purpose of this study was to determine the phytochemical content of Oncidium Aliceara alice and its activity in wound healing when it is formulated in a gel form. This research is experimental research with extraction stages, phytochemical assay, gel formulations, quality test, and wound healing activity tests in animals. The gel formulation was made with various concentrations of Oncidium Aliceara alice extract 2.5%, 5% and 10%. Male Sprague Dawley rats were given an incision wound on the dorsum of the longitudinal axis along 3 cm. Wound care by administering topical Bioplacenton as a positive control, base gel as a negative control, and gel extract concentration variants according to each treatment group. Based on the research, the results of qualitative phytochemical tests showed that the 70% ethanol extract of Oncidium Aliceara alice contains flavonoids (catechins), tannins, steroids, and saponins. The best results were seen on the 7th day of observation for the 10% gel extract treatment group with more perfect signs of wound closure than the bioplacenton treatment.